Analisis Pelatihan Karyawan PT XYZ - Syaifullah Abrar; Christian Wiradendi Wolor; Eka Dewi Utari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to evaluate the effectiveness of employee training at PT XYZ, particularly in enhancing work performance and motivation. The research employs a descriptive qualitative method using purposive sampling. Informants consist of one team leader and three staff members selected through in-depth interviews, observation, and documentation. The results indicate that the training provided remains one-way, lacks interactivity, and is not entirely relevant to employees’ daily tasks. This leads to low motivation and minimal effectiveness in improving performance. Several challenges were also identified, including the absence of post-training follow-up, monotonous delivery methods, and limited time due to workload constraints. The study suggests that organizations should improve their training systems by aligning materials with job relevance, adopting more engaging methods, and ensuring continuous support from management.